A new species of Cephalanticoma (Enoplida: Anticomidae) from Brazilian coast (Atlantic Ocean), with emended diagnosis and dichotomous key to the genus - Manoel, Alex; Esteves, André M.; Maria, Tatiana F. (Zootaxa, 2020)
A new species of the genus Cephalanticoma is described for the Atlantic Ocean in the Potiguar Basin off the continental shelf of northeast Brazil. Cephalanticoma rugatusa sp. n. is characterized by bearing head capsule ending on the level of amphideal fovea, a tubular precloacal supplement and two rows of thin precloacal setae. Cephalanticoma rugatusa sp. n. differs from all other species of the genus by having a precloacal cuticular papilla in front of the cloaca and a cuticular transversal wrinkle which extends from the papilla elevation to the conical-cylindrical portion of the tail occupying both subventral regions. An emended diagnosis and a dichotomous key to species based on both genders are provided.